2020
DOI: 10.1111/cas.14300
|View full text |Cite
|
Sign up to set email alerts
|

Dual antivascular function of human fibulin‐3 variant, a potential new drug discovery strategy for glioblastoma

Abstract: The ECM protein EFEMP1 (fibulin‐3) is associated with all types of solid tumor through its cell context‐dependent dual function. A variant of fibulin‐3 was engineered by truncation and mutation to alleviate its oncogenic function, specifically the proinvasive role in glioblastoma multiforme (GBM) cells at stem‐like state. ZR30 is an in vitro synthesized 39‐kDa protein of human fibulin‐3 variant. It has a therapeutic effect in intracranial xenograft models of human GBM, through suppression of epidermal growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…An increasing number of studies have shown that GSCs play a vital role in the development of VM in glioma. 41 However, Ke et al 42 found that non-stem-like cells of glioma were more prone to gain VM-related gene expression and phenotype than were stem-like cells of the same origin.…”
Section: Differentiation Of Glioma Stem Cells (Gscs)mentioning
confidence: 99%
“…An increasing number of studies have shown that GSCs play a vital role in the development of VM in glioma. 41 However, Ke et al 42 found that non-stem-like cells of glioma were more prone to gain VM-related gene expression and phenotype than were stem-like cells of the same origin.…”
Section: Differentiation Of Glioma Stem Cells (Gscs)mentioning
confidence: 99%
“…EFEMP1 is secreted by glioma cells to promote angiogenesis, tumor invasion, and tumor cell survival. The development of blocking antibodies against EFEMP1 or truncation variants and other mutants by gene engineering may more be an effective therapeutic approach for malignant gliomas [25] , [26] . However, in breast cancer [27] and endometrial cancer [28] , [29] , EFEMP1 acts as a tumor suppressor gene, Low EFEMP1 levels predict adverse outcomes, and high EFEMP1 levels inhibit TGF-β-induced EMT, migration, and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Matrigel has also shown utility in the study of GSC transdifferentiation into ECs. A tubular network assay with patient-derived GBM cells cultured on Matrigel was used to characterize GSCs and verify their vascular development ability (Ke et al, 2020). In this case, patient cells were able to transdifferentiate into ECs and further form tubular structures.…”
Section: Scaffold-based Modelsmentioning
confidence: 99%
“…In this case, patient cells were able to transdifferentiate into ECs and further form tubular structures. Using the same model, researchers also tested drugs capable of inhibiting this transdifferentiation process (Ke et al, 2020). Furthermore, patient-derived GBM cells cultured on Matrigel have also been used to study GBM recurrence and resistance mechanisms after radiotherapy.…”
Section: Scaffold-based Modelsmentioning
confidence: 99%